'Improper Grimoires' Evelyn Underhill's Representation of Ritual Magic in The Column of Dust - Pazdziora, J. Patrick (2019)
Evelyn Underhill (1875-1941) is generally regarded as a piously Anglican writer; her interest in the occult is either elided or dismissed as unserious dabbling. An examination of her writings on the subject, however, reveals a keen, intelligent curiosity about the theory and practice of ritual magic. Underhill studied the occult in real depth, eventually fictionalising a conjuration in her novel The Column of Dust (1909). Underhill saw the occult not merely as the preserve of cranks and charlatans, but as a coherent system of belief which provided a sense of power and independence for women constrained by middle-class social structures.